2016
DOI: 10.1007/s00296-016-3603-3
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of specific exercise types on cardiopulmonary functions in patients with ankylosing spondylitis: a systematic review

Abstract: The aim of this review was to assess the effectiveness of specific exercise types on pulmonary functions, aerobic and functional capacity in patients with ankylosing spondylitis (AS). A systematic search of Cochrane Database of Systematic Review, MEDLINE (EBSCO), Physiotherapy Evidence Database (PEDro), CINAHL (EBSCO), PUBMED, AMED, EMBASE (OVID) was conducted in January 2016. The outcome measures were spirometric measurements, chest expansion, 6 minute walk distance (6MWD), pVO, Bath Ankylosing Spondylitis Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Vigorous CRT corresponds to 65-90% of maximum heart rate or energy expenditure of ≥6 metabolic equivalents for ≥20 minutes performed ≥3 days/week (5). Recent studies in patients with AS showed that vigorous CRT, in appropriate frequency and duration, was effective with regard to cardiovascular fitness, as well as being safe and feasible (10), and may have an impact on disease activity and CVD risk (11). Therefore, the Swiss patient organization for patients with axial SpA (Schweizerische Vereinigung Morbus Bechterew [SVMB]) aims to implement vigorous CRT in their ~80 exercise groups with >600 participants throughout Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…Vigorous CRT corresponds to 65-90% of maximum heart rate or energy expenditure of ≥6 metabolic equivalents for ≥20 minutes performed ≥3 days/week (5). Recent studies in patients with AS showed that vigorous CRT, in appropriate frequency and duration, was effective with regard to cardiovascular fitness, as well as being safe and feasible (10), and may have an impact on disease activity and CVD risk (11). Therefore, the Swiss patient organization for patients with axial SpA (Schweizerische Vereinigung Morbus Bechterew [SVMB]) aims to implement vigorous CRT in their ~80 exercise groups with >600 participants throughout Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, exercise therapy should be considered for patients with AS, since spine and chest stiffness and decreased respiratory system functions and motor ability due to chest wall alterations may occur 13 14) . Advantages of exercise therapy include: i) providing aerobic workout, ii) physical training, which promotes spine flexibility, strength endurance and pulmonary function 12 15) , and iii) reducing the risk of cardiopulmonary complications 16) .…”
Section: Ankylosing Spondylitismentioning
confidence: 99%
“…In addition to the medical treatments, specific exercise therapy might reduce the cardiopulmonary complications related with AS. 18 While moderate evidence supports exercise interventions in improving physical function, disease activity and chest expansion compared to controls; there is low-level evidence of improved pain, stiffness, spinal mobility and cardiorespiratory function. Supervised group exercise provides more beneficial outcomes than unsupervised home exercise.…”
Section: Electrical Therapymentioning
confidence: 99%
“…The search was limited to articles in the English language, starting from the earliest papers to May 2017 and carried out from the scientific search guidelines published in 2011. 12 Since there are already published reports in the literature for inflammatory rheumatic diseases, [13][14][15][16][17][18][19] we did not plan to address this issue in this article. Because the literature was scarce in AIDs, this overview contains general information and brief descriptions on some of the clinical entities of AIDs which are commonly encountered in the Physical and Rehabilitation Medicine (PRM) branch, particularly due to musculoskeletal involvement.…”
Section: Introductionmentioning
confidence: 99%